The burden of atherosclerosis in Portugal - Costa, João (2021)
AIMS: This article sought to estimate the burden of disease attributable to atherosclerosis in mainland Portugal in 2016. METHODS AND RESULTS: The burden of atherosclerosis was measured in disability-adjusted life years following the latest 2010 Global Burden of Disease (GBD) methodology. Disability-adjusted life years were estimated as the sum of years of life lost (YLL) with years lived with disability (YLD). The following clinical manifestations of atherosclerosis were included: ischaemic heart disease (IHD) (including acute myocardial infarction, stable angina, and ischaemic heart failure), ischaemic cerebrovascular disease (ICVD), and peripheral arterial disease (PAD). Years of life lost were estimated based on all-cause mortality data for the Portuguese population and mortality due to IHD, ICVD, and PAD for the year 2016 sourced from national statistics. Standard life expectancy was sourced from the GBD study. Years lived with disability corresponded to the product of the number of prevalent cases by an average disability weight for all possible combinations of disease. Prevalence data for the different clinical manifestations of atherosclerosis were sourced from epidemiological studies. Disability weights were sourced from the published literature. In 2016, 15 123 deaths were attributable to atherosclerosis, which corresponded to 14.3% of overall mortality in mainland Portugal. Disability-adjusted life years totalled 260 943, 75% due to premature death (196 438 YLL) and 25% due to disability (64 505 YLD). CONCLUSION: Atherosclerosis entails a high disease burden to society. A large part of this burden would be avoidable if evidence-based effective and cost-effective interventions targeting known risk factors, from prevention to treatment, were implemented.